12-lead ECG in the athlete: physiological versus pathological abnormalities - Corrado, D.; Biffi, A.; Basso, C.; Pelliccia, A.; Thiene, G. (British Journal of Sports Medicine, 2009)
Participation in sports activity and regular physical training is associated with physiological structural and electrical changes in the heart (athlete`s heart) that enable sustained increases in cardiac output for prolonged periods. Cardiovascular remodelling in the conditioned athlete is often associated with ECG changes. In rare cases, abnormalities of an athlete`s ECG may reflect an underlying heart disease which puts the athlete at risk of arrhythmic cardiac arrest during sport. It is mandatory that ECG abnormalities resulting from intensive physical training and those of a potential cardiac pathology are properly defined. This article provides a modern approach to interpreting 12-lead ECGs of athletes based on recently published new findings. The main objective is to distinguish between physiological adaptive ECG changes and pathological ECG abnormalities. The most important aims are to prevent physiological changes in the athlete being erroneously attributed to heart disease, or signs of life-threatening cardiovascular conditions being dismissed as a normal variant of athlete`s heart. As pathological ECG abnormalities not only cause alarm but also require action with additional testing to exclude (or confirm) the suspicion of a lethal cardiovascular disorder, appropriate interpretation of an athlete`s ECG will prevent unnecessary distress and also result in considerable cost saving in the context of a population-based preparticipation screening programme.